(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article is devoted to the study of the effectiveness of mobile robotics in providing first aid in emergency situations in the coal industry. The work analyzes the design principles of robotic systems, sensor and control modules, motion mechanisms and safety systems. The results of laboratory and field tests are also presented, their effectiveness and practical application are evaluated. The article proposes new technological approaches to quickly detect emergency situations in coal mines, protect human workers from dangerous zones and quickly provide first aid. The research results show the possibilities, limitations and development prospects of using robotics in an industrial environment.